Trilateral Retinoblastoma in a Patient With Peutz–Jeghers Syndrome. Issue 5 (5th March 2013) - Raizis, Anthony M.; Van Mater, David; Aaltonen, Lauri A.; Lohmann, Dietmar; Cheale, Michelle S.; Bickley, Vivienne M.; George, Peter M.; Zhou, Yaolin; Rosoff, Philip M.
Abstract Germline loss of function mutations in tumor suppressor genes RB1 and LKB1/STK11 are associated with the autosomal dominant cancer predisposing syndromes familial retinoblastoma and Peutz–Jeghers syndrome (PJS), respectively. We present a rare case of a young woman with trilateral retinoblastoma diagnosed as an infant who survived and was then diagnosed with PJS as a teenager. There was no family history of either disorder. Analysis of the LKB1/STK11 gene sequence identified a germline frameshift mutation (c.107del) leading to a nonsense mutation near the N‐terminus of the protein, confirming a clinical diagnosis of Peutz–Jeghers syndrome. Extensive RB1 gene analysis failed to detect germline mutations or deletions, and immunohistochemical analysis of her ocular tumors demonstrated nuclear staining of immunoreactive pRB. This result suggests that the RB1 gene is intact. We estimate the chance of trilateral retinoblastoma and PJS occurring in the same individual at approximately 1 in 134 billion live births, and we discuss the possibility that this case could be explained by a putative modifier of pRB action that is associated with the LKB1/STK11 pathway. © 2013 Wiley Periodicals, Inc.